Pengaruh Berkumur Ekstrak Daun Salam (Eugenia polyantha Wight) terhadap Pembentukan Plak Gigi - Irmanita Wiradona; Erni Mardiati; Sariyem Sariyem (Jurnal Riset Kesehatan, 2015)
The aim of this study was to determine the effect of bay leaf extract mouthwashes on plaque formation. This type of research was experimental with pretest and posttest control group design. The number of samples was 30 students of class V SDN Meteseh, Tembalang, Semarang. The samples were divided into two groups, group I were rinsed with salam leaf extract and group II distilled water rinse. Plaque was measured using the plaque index by PHP before and after rinsing leaves extract. Analysis of the data used is the Independent Sample t - Test. The test results showed that the value of p = 0,000 which means a decrease in plaque index occurs significantly in the control and treatment groups. Independent Sample t - Test showed that the value of p = 0,005 so there was a significant difference between the control group  rinsed with distilled water rinse treatment group to the salam leaf extract (Eugenia polyantha Wight). It can be concluded that gargling salam leaf extract could reduce the formation of dental plaque.